2003
DOI: 10.1074/jbc.m212210200
|View full text |Cite
|
Sign up to set email alerts
|

The 1.92-Å Structure of Streptomyces coelicolor A3(2) CYP154C1

Abstract: Evolutionary links between cytochrome P450 monooxygenases, a superfamily of extraordinarily divergent heme-thiolate proteins catalyzing a wide array of NADPH/NADH-and O 2 -dependent reactions, are becoming better understood because of availability of an increasing number of fully sequenced genomes. Among other reactions, P450s catalyze the site-specific oxidation of the precursors to macrolide antibiotics in the genus Streptomyces introducing regiochemical diversity into the macrolide ring system, thereby sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 62 publications
2
41
0
Order By: Relevance
“…This structure revealed that the protein can adopt a wide open conformation, allowing direct transfer of substrates from the protein exterior to the active site. This open cleft was grossly similar to openings observed in a few recent bacterial P450 structures (4,5) and was stabilized by dimerization of the protein, which occurs both in the crystals and in solution. In the symmetric homodimer, a portion of one molecule (helices FЈ-GЈ) partially fills the cleft of the second molecule, with His-226 forming an intermolecular coordinate bond to the sixth position of the heme iron.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This structure revealed that the protein can adopt a wide open conformation, allowing direct transfer of substrates from the protein exterior to the active site. This open cleft was grossly similar to openings observed in a few recent bacterial P450 structures (4,5) and was stabilized by dimerization of the protein, which occurs both in the crystals and in solution. In the symmetric homodimer, a portion of one molecule (helices FЈ-GЈ) partially fills the cleft of the second molecule, with His-226 forming an intermolecular coordinate bond to the sixth position of the heme iron.…”
supporting
confidence: 81%
“…A few recent bacterial structures, however, suggest a "lid" domain composed of helices F and G, the motion of which controls substrate entry (3)(4)(5). Protein flexibility has also been implicated in dictating the regiospecificity of oxidation once a substrate is present in the active site.…”
mentioning
confidence: 99%
“…Together with the F helices, they constitute two layers of anti-parallel ␣-helices crossing each other at an angle of ϳ60°. A similar dimerization pattern, although with a smaller (600 Å 2 , 3.5% of the monomer surface) dimerization interface, is observed in ligand-free CYP154C1 (45) (Fig. 5B).…”
Section: Protein-protein Interactions and Bindingsupporting
confidence: 68%
“…Two potential sources of CYP130 binding cooperativity can be considered as follows: (i) multiple site cooperativity, in which two or more ligands bind simultaneously to the same protein molecule, and (ii) multimer cooperativity, where protein-protein interactions are pro- (45). Stoichiometry of CYP130 Inhibitor Binding-To address the possibility that binding cooperativity may arise from the binding of multiple inhibitor molecules in the CYP130 active site, the stoichiometry for the CYP130-econazole and CYP130-miconazole complexes was determined using the Job's titration method (22), which is based on mixing of the reactants in such a way that their molar ratio varies, whereas the total molar concentration remains constant.…”
Section: Expression and Purification Of Cyp130-cyp130mentioning
confidence: 99%
“…The structure of two CYP154 enzymes from Streptomyces coelicolor A3(2), CYP154C1 and CYP154A1, has already been elucidated by X-ray crystallography (18,19). CYP154C1 has been shown to convert the 12-and 14-membered ring macrolides, narbomycin and YC-17, into pikromycin and neomethymycin, respectively, in vitro (18); however, not enough substrate screening of CYP154C1 has been performed.…”
mentioning
confidence: 99%